Tales of the Orishas - Canuto, Hugo, 1986- (Abrams ComicArts, an imprint of ABRAMS, 2023)
"In ancient times, when heaven and Earth were united as two halves of a gourd, deities and heroes walked among men. They fought battles with fury and taught the ways of the ashe (the energy of creation), land, iron, and fire. They reigned and loved with great intensity. Some descended from the luminous Orun, to live their lives and fulfill their destinies, while others were born in the aiye, and through their great deeds became Orishas, changing forever the history of two continents. Tales of the Orishas fuses the pantheon of the African diasporic religion of Candomblé with the Silver Age comic aesthetics of Jack Kirby into a riveting tale of high adventure. The story centers around a celestial battle between the gods of Brazil, who are worshipped by the Bahia people, and a fearsome conquering force led by a dark and malevolent overlord. Only Shango, the god of fire and thunder, can lead his people into victory while the fate of creation hangs in the balance."--